Pengaruh Kompres Hangat Terhadap Intensitas Nyeri Pada Lansia Yang Mengalami Reumatoid Artritis Di Desa Kotasan Kecamatan Galang - Damanik, Devi Novita (Universitas Aufa Royhan, 2019)
Rheumatoid arthritis (RA) is a chronic disease that causes pain, stiffness, swelling and limited mobility and function of many joints. One way to reduce complaints of pain due to RA in the elderly can be done with nonpharmacological measures. Non-pharmacological actions performed, namely a warm compress by warming the diseased joints. The purpose of this study was to determine the effect of warm compresses on pain intensity in the elderly who experience RA in Desa Kotasan Kecamatan Galang. This research is a quantitative study using a quasi-experimental research design. The design of this study is the pretest-posttest control group design, which is to make a comparison between the intervention group and the control group before and after the intervention is given. The researcher measured the pain scale of the respondent by using the pain scale then gave an intervention in the form of a warm compress to the respondent. The results of the independent t test compared the average value of the pain group of the intervention group and the control group on the post test score showed the mean post test score of the intervention group was 15.96 and the average value of the control group was 23.08 with a calculated value = - 5.779 with a p value of 0.000 (p <0 , 05). This shows that there are differences in the mean value of pain between the intervention group and the control group. The conclusion is that there is an effect of giving a warm compress to a decrease in pain level in elderly patients with RA pain complaints.